Razonamiento lógico y su incidencia en el aprendizaje de matemática en los estudiantes de quinto a décimo año de educación básica de la Escuela “Nuestra Señora de la Natividad”, año lectivo 2015 – 2016. Talleres de capacitación. - Espinoza Delgado, Leonor de Jesús (2016)
Basic Education School "Our Lady of the Nativity" is located in Quevedo, Los Rios Province, Canton's mission is to train students with moral principles and spiritual values. It is an institution with 12 years of experience and has been a contribution to the formation of the youth of this part of the province of Los Rios. The Constitution and new laws education has many changes, the most important decentralization or transfer of responsibilities and resources from the central government to the provincial governments, municipal and parish and especially the institutions themselves, ie skills and powers from national to their district levels are coordinating. The objective of this research was to evaluate the incidence of logical reasoning in mathematics learning among students in fifth to tenth year of basic education of "Our Lady of the Nativity" School which proposed alternative solutions. Methodology applied for information gathering and evaluation were new support techniques such as surveys, obtaining in the latter, information provided directly by students, teachers and parents, interviews directly with the respective district authorities. This research contributed to solving the problems as was to design training workshops for teachers in mathematics logical reasoning. Purposeful, meet social and educational needs that favor as the foundation and source is the institution with the commitment and responsibility to socialize recipients.